2015
DOI: 10.1515/revneuro-2014-0076
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Alzheimer’s disease

Abstract: AbstractAutophagy is a vesicle and lysosome-mediated degradative pathway that is essential for protein homeostasis and cell health. In particular, compared to nonneuronal cells, neurons are dependent on high basal autophagy for survival. There is emerging agreement that defects in autophagy are likely to contribute to the neurodegenerative processes in numerous diseases, including Alzheimer’s disease (AD). Autophagy-lysosome defects occur early in the pathogenesis of AD and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(151 citation statements)
references
References 114 publications
(153 reference statements)
1
148
0
2
Order By: Relevance
“…Multiple researchers have verified that increased activity of the autophagy pathway leads to increased degradation of the tau protein and hence reduced intracellular tau aggregation [53]. Nevertheless, the molecular interaction between autophagy and Aβ remains controversial.…”
Section: Major Cancer-related Signaling Pathways With Links To Ad mentioning
confidence: 99%
“…Multiple researchers have verified that increased activity of the autophagy pathway leads to increased degradation of the tau protein and hence reduced intracellular tau aggregation [53]. Nevertheless, the molecular interaction between autophagy and Aβ remains controversial.…”
Section: Major Cancer-related Signaling Pathways With Links To Ad mentioning
confidence: 99%
“…These observations may be significant in terms of differentiating AD from normal ageing, as there is copious evidence that the autophagic process is downregulated in normal ageing [288,289]. However, despite the transcriptional upregulation of autophagy seen in AD patients, the weight of evidence indicates that autophagic lysosomal clearance is dysregulated and defective in the hippocampus of AD patients, even in those in the very early stages of their disease [287] [24].…”
Section: Oxidative Stress Mtor Activation and Impaired Autophagy And mentioning
confidence: 99%
“…Other commonly reported abnormalities include compromised autophagy and lysosomal clearance accompanied by elevated activity of both glycogen synthase kinase-3 (GSK-3) and mechanistic (previously mammalian) target of rapamycin (mTOR), coupled with a defective ubiquitin-proteasome system (UPS) [12,[23][24][25][26][27]. Several authors have also reported abnormalities in the activity of several kinases and phosphatases, most notably mitogen-activated protein kinases (MAPKs) and protein phosphatase 2A (PP2A or PP2), and transition metal dyshomeostasis, which could all arguably play a role, either as primary or secondary drivers of disease activity [11-13, 16, 28-30].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy negatively regulates inflammation. Increased activity of the autophagy pathway leads to increased degradation of the tau protein and hence reduced intracellular tau aggregation [49], suggesting that the aberrant accumulation of tau proteins may, at least in part, be due to impaired autophagy inside neurons [54]. Another major protective role of autophagy is the elimination of abnormal mitochondria, a source of oxidative stress.…”
Section: Autophagy In Ad Genesismentioning
confidence: 99%
“…Evidence is presented suggesting amyloid oligomers as necessary but insufficient causes of the dementia and that, for dementia to develop, additional cofactors are required [13]. Those cofactors include several subcellular processes including oxidative damage [10,[14][15][16][17][18][19][20][21][22][23], recruitment of peripheral immune cells and excessive production of pro-inflammatory mediators [10,[24][25][26][27][28][29], mitochondrial impairments and chronic energy imbalance [12,20,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], chronic endoplasmic reticulum (ER) stress [48] and autophagy dysfunction [22,[49][50][51][52][53][54], the abnormality and dysfunction of MAM (the mitocho...…”
Section: Introductionmentioning
confidence: 99%